Pengaruh Insight pada Proses Kesembuhan pasien Skizofrenia - Wulansari NMA (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction; mental disorders are still a serious problem in today's world. Aim; know the effect of insight on the healing process of schizophrenia patients. Method; The research design uses a case study that aims to describe the nursing care carried out. Result; shows the results of observations of patients who are not aware that they have schizophrenia, have been in and out of the hospital because of schizophrenia. Conclusion; that schizophrenia is a serious mental disorder that requires intensive treatment